ALASAN REMAJA PUTRI MELAKUKAN PERNIKAHAN USIA DINI - Ribkha Itha Idhayanti; Cristiani Tamu Apu; Esti Handayani (Universitas Respati Yogyakarta, 2020)
Background: High level of marriage Early age prevalence at the world level, Indonesia ranks 37th and 2nd highest in ASEAN, age of first marriage in Central Java Province, 51.1% occurs at the age from 10-14 years, the impact of early marriage itself more evident in young women compared to young men in Temanggung Regency, Marriage at the age of <16 young women recorded 47 people (0.84%) and ages 16-19 years recorded 1418 people (25.4%), in Bulu Distict there were 97 people (89.8%) and the most in Gandorejo village, in 2017 there were 7 people (3.43%) and in 2018 there were 28 people (13.72%).Objective: to determine the level of relationship between the knowledge of early marriage and the reason for getting married regard to the motivation early marriage of young women.Methods: Analytical survey using Cross Sectional approach or cross cut. The subjects in this study were girls aged 15-19 years who were not married with the sampling technique using stratified sampling random sampling technique. by of 67 respondent from 201 populatio. Results: There was a correlation between the level of knowledge about early marriage and the motivation of young women to do early marriage with p value 0.037 and there was no relationship between the reasons for early marriage and the motivation of young women to do early marriage with p value 0.437.Conclusion: there was a correlation between the level of knowledge about early marriage and the motivation of young women to do early marriage